HERITABILITY AND GENETIC VARIABILITY FOR YIELD COMPONENTS UNDER TWO REGIMES OF SOIL IN BARLEY (HORDEUM VULGARE L.) - R. S. RAIKWAR; A. K. UPADHYAY; P. K. TYAGI (The Bioscan, 2014)
The present investigation was undertaken to evaluate the variability of heritability and genetic variability for 15 morphological traits including yield and quality of six generations in barley crosses under two soil conditions with ten genetically divers varieties of barley in randomized block design with three replications during winter season 2012-2013. The results indicated that the heritability percentage in narrow sense to broad sense ranged varied from 5.19 h2n (plant height) to 99.75 h2b (number of grains/spike). High heritability percentage (>75 h2b) coupled with high genetic variability percentage (>40 Ga) were recorded for weight of grains/main spike in cross I (92.98 h2b and 50.10 Ga) and cross III (96.39 h2b and 54.75 Ga), number of grains/spike in cross V (92.90 h2 b and 54.20 Ga), grain yield/plant in cross I (98.90 h2b and 44.97 Ga), cross II (99.24 h2b and 62.71 Ga) and cross III (98.87 h2 b and 47.43 Ga), respectively under normal soil. The traits, number of effective tiller/plant in cross I (97.06 h2b and 45.67 Ga) and cross III (97.39 h2b and 57.48 Ga), weight of grains/spike in cross IV (94.60 h2b and 50.05 Ga)), grain yield per plant in cross II (99.22 h2 b and 71.23 Ga), cross III (99.10 h2b and 55.80 Ga) and cross IV (94.54 h2b and 51.49 Ga), respectively and lysine content in cross III (75.06 h2b and 43.96 Ga) had high heritability with high genetic variability under saline sodic soil. It was concluded that 12 cases showed high heritability (h2b) percentage coupled with high genetic variability particularly grain yield/plant in cross I (DL 88 x K 560) and cross II (K 603 x Azad) under normal situation and emerged as ideal traits for improvement through simple selection in succeeding generations.